PANI-grafted radially porous MnO2 for supercapacitor applications - Sinan-Tatli, Neriman; Unur-Yilmaz, Ece (Springer, 2024)
In this study, manganese carbonate (MnCO3) microspheres were used as self-templates for the synthesis of hollow and radially porous MnO2 via an oxidation-etching process. Then, in situ polymerization of aniline was conducted with and without 3-aminopropyl triethoxysilane (APTES) grafting agent, resulting in the formation of PANI-grafted MnO2 (MGP) and PANI-coated MnO2 (MP), respectively. The electrochemical performances were evaluated in a three-electrode configuration using a 1 M H2SO4 aqueous electrolyte solution. Both samples showed high-specific capacitances owing to the unique MnO2 structure with radial cavities, which facilitate ion diffusion and effectively accommodate volume expansion during cycling. The MGP exhibited similar to 30% higher specific capacitance (765 F g(-1) and 586 F g(-1) at 0.25 A g(-1)) and extended cycle life (80% retention after 14,000 cycles) compared to the MP. The results demonstrate that the charge transfer efficiency and structural stability of MGP are enhanced by the formation of covalent bonds between MnO2 and PANI through grafting.
Keywords: MnCO3; MnO2; PANI grafting; Self-template; Supercapacitors